Phonological and Morphological Factors of Indonesian Children's Stuttering - Rahmalina, Reny; Sudana, Dadang; Arianingsih, Anisa; Sunendar, Neidya Fatma; Saifullah, Aceng Ruhendi (Humanus, 2023)
The aim of this research is to examine whether there is an influence of children who stutter (CWS) on linguistic factors (phonology and morphology) in Indonesian. This research is a case study research with quantitative methods. The method used was: five CWS were directed to spontaneously speak Indonesian with a stuttering examination validated by a speech expert. Transcribe recordings and mark stutters. Next, words included in the stuttering category were analyzed for their phonological and morphological characteristics. The results showed that words starting with a phoneme and a consonant in the initial position of the word had a higher level of stuttering. Word length, word class, and inflection at the end of the word did not have a significant effect on the level of CWS stuttering. Stuttering can occur in many languages and the linguistic structure of speakers varies.